2021
DOI: 10.1155/2021/9227897
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Role of the Neuropeptide LGI1 Receptor ADAM23 in Regulating Biomarkers of Ferroptosis and Progression of Esophageal Cancer

Abstract: Background. According to recent studies, ferroptosis is closely related to the efficacy and prognosis of tumour treatment. However, the role of ferroptosis in esophageal squamous cell carcinoma (ESCC) has not been explored comprehensively. Materials and Methods. The esophageal cancer (EC) transcriptome data was downloaded from The Cancer Genome Atlas (TCGA), then analyzed, to obtain the differentially expressed messenger RNA (mRNA), microRNA (miRNA), and long noncoding RNA (lncRNA) between groups with the low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…MicroRNAs (miRNAs) belong to a family of non-coding RNAs of 20-24 nucleotides in length. MiRNAs are significantly associated with tumor development and metastasis (Liu et al, 2019;Wang et al, 2019;Chen et al, 2021;Zhang and Liu, 2021;Cao et al, 2022). Compared with normal tissues, miRNA expression is down-regulated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) belong to a family of non-coding RNAs of 20-24 nucleotides in length. MiRNAs are significantly associated with tumor development and metastasis (Liu et al, 2019;Wang et al, 2019;Chen et al, 2021;Zhang and Liu, 2021;Cao et al, 2022). Compared with normal tissues, miRNA expression is down-regulated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Many biomarkers for EC have been reported [ 5 7 ]. However, some studies reported lymph node metastases patterns at the time of surgery [ 8 , 9 ], and to attribute the recurrence/metastasis patterns and death patterns of advanced EC to patients' clinical characteristics is still a big challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In the TCGA nM-LUAD dataset, we used the GSVA package to calculate the enrichment scores of ferroptosis-related gene sets (including ACSL4, ALOX15, COQ10A, COQ10B, FDFT1, GPX4, HMGCR, SLC3A2, SLC7A11, NFE2L2, NOX1, NOX3, NOX4, and NOX5 ). This followed the ferroptosis index (FPI) calculation by applying the standardized method as described previously ( 40 , 41 ). These FPI scores are used to quantify the likelihood of ferroptosis of cells within a tumor or tissue and based on median FPI scores, nM-LUAD patients are divided into high and low FPI groups.…”
Section: Methodsmentioning
confidence: 99%